Effect of ground steel slag powder on cement properties. (April 2015) - Liu, F.; Chen, M. Z.; Li, F. Z.; Li, Q. L.; Wu, S. P.; Sang, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> The work aims to evaluate the influences of steel slag's fineness and particle-size distribution on the properties of cement-based materials. The materials used for this study included Portland cement and steel slag powder with seven different specific surface areas. The properties of cement pastes and mortars with steel slag powder were tested including water requirement of normal consistency, setting time, fluidity, soundness, compressive and flexural strength. The experimental results show that the influence of steel slag powder on water requirement of normal consistency of cement is in relation to its specific surface area, and the value of decreases for steel slag powder with a lower-specific surface area while increases with a higher-specific surface area. The partial replacement of cement by steel slag powder decreases the strength of cement, but increases the ratio of flexural to compressive strength and thus improves the ductility of cement-based materials.